PENGEMBANGAN MADING DIGITAL BERMUATAN QR-CODE UNTUK MENUMBUHKAN LITERASI SEJARAH KELAS XI DI SMA AL-ISLAM KRIAN - Syalwa Shabrina Khunaifi; Corry Liana (Prabayaksa: Journal of History Education, 2026)
Low student interest in history learning and limited use of interactive learning media hinder the development of historical literacy in schools. This study aimed to develop a QR-code-based digital wall magazine, evaluate its feasibility, and examine students’ historical literacy achievement after its implementation. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Qualitative data were collected through observation, interviews, and documentation, while quantitative data were obtained from expert validation sheets, student response questionnaires, and historical literacy assessment instruments. Data were analyzed descriptively using percentage calculations for media feasibility and historical literacy achievement, while questionnaire validity and reliability were tested using IBM SPSS. The results showed that the developed digital wall magazine achieved a feasibility score of 84% from media experts and 100% from material experts, both categorized as very feasible. Student responses reached an average score of 90.25%, indicating a very positive perception of the media. Furthermore, students’ historical literacy achievement reached an average of 76.31%, categorized as good based on twelve historical literacy indicators. These findings indicate that the QR-code-based digital wall magazine is a feasible and effective supplementary learning medium that provides interactive and accessible digital learning resources for history education and supports the development of students’ historical literacy.